Antibacterial Property of a Coral-Associated Bacterium Pseudoalteromonas luteoviolacea Against Shrimp Pathogenic Vibrio harveyi (In Vitro Study) - OCKY KARNA RADJASA; TORBEN MARTENS; HANS- PETER GROSSART; AGUS SABDONO; MEINHARD SIMON; TONNY BACHTIAR (HAYATI Journal of Biosciences, 2005)
A coral-associated bacterium was successfully screened for secondary metabolites production based on PCR amplification of the nonribosomal peptide synthetase gene and was identified as closely related to Pseudoalteromonas luteoviolacea based on its 16S rDNA.The bacterium was found to inhibit the growth of shrimp pathogenic bacterium tested, Vibrio harveyi. To characterize the inhibiting metabolite, a 279 bp long DNA fragment was obtained and the deduced amino acid sequence showed conserved signature regions for peptide synthetases and revealed a high similarity to NosD (40% identity), a multifunctional peptide synthetase from Nostoc sp. GSV224, and NdaB (44% identity), a peptide synthetase module of Nodularia spumigena.